Memahami Esensi Asmaul Husna dalam Alqur’an (Implementasinya Sebagai Ibadah dalam Kehidupan) - R, Abd Rahman (Jurnal Adabiyah, 2011)
Something important to know is understanding Asmaul Husna in al-Quran. This writing discusses some points of al-Asma a-Husna that contains close meaning with the values of human life. Mankind will be more progress, civilized, prosperious and can stand on its own feet, if they always implement the values of Asmaul Husna, both indivually or socially, this is because Asmaul Husna is the essence or heart of religion. Thus, Allah has ever reminded those who do shalat (pray) to implement its values in daily life. The values of shalat are reflected in Asmaul Husna.